2024
DOI: 10.1108/jarhe-09-2023-0445
|View full text |Cite
|
Sign up to set email alerts
|

Investigating student’s motivation and online learning engagement through the lens of self-determination theory

Adedapo Oluwaseyi Ojo,
Sumitha Ravichander,
Christine Nya-Ling Tan
et al.

Abstract: PurposeThe lack of physical contact and the absence of nonverbal clues could make some learners uncomfortable interacting with others via online learning platforms. Hence, understanding the determinants of students' motivation and engagement in online learning platforms is crucial in harnessing digital technology as an enabler of unrestricted and quality learning experiences.Design/methodology/approachDrawing on the self-determination theory (SDT), this study investigates the factors associated with student’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The study found that perceived ability and emotional engagement have a significant impact on students who complete MOOCs, and different dimensions of learning engagement can predict learners’ perceived learning effectiveness. Meanwhile, in the online learning environment, significant changes have occurred in the way students interact with teachers and peers, which requires educators to pay more attention to cultivating students’ autonomous learning abilities, computer and network skills, and online communication abilities to promote their learning engagement 21 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that perceived ability and emotional engagement have a significant impact on students who complete MOOCs, and different dimensions of learning engagement can predict learners’ perceived learning effectiveness. Meanwhile, in the online learning environment, significant changes have occurred in the way students interact with teachers and peers, which requires educators to pay more attention to cultivating students’ autonomous learning abilities, computer and network skills, and online communication abilities to promote their learning engagement 21 .…”
Section: Literature Reviewmentioning
confidence: 99%